IMPLEMENTATION OF KAMPUS MENGAJAR 4 PROGRAM TO EQUALIZE THE QUALITY OF BASIC EDUCATION AT FIRST SEKUNYIT PUBLIC ELEMENTARY SCHOOL - Suhardiman, Arif; Liastamin, Anwar; Alambana, Bondan Muhammad; Kurniawansyah, Edy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
The fourth teaching campus program is one of the MBKM programs from the Indonesian Ministry of Education and Culture. It was carried out by students in groups at placement schools, one at First Sekunyit Public Elementary School. The method used in this research is descriptive qualitative research, carried out by students planning and going directly to placement schools and carrying out activity programs. This program aims to help schools learn literacy and numeracy, adopt technology, and assist school administration. The result of implementing the KM4 program is that students help teach literacy and numeracy through various activity programs in the form of helping teach in class, carrying out class AKM (minimum competition assessment), numeracy literacy corner, talent interest development, and natural school. Judging from helping adapt technology, KM4 students carry out learning activities that are integrated with the use of innovative learning media. As for assisting administration, the implementation is in the form of data collection on students who receive BIP (competent Indonesian assistance) funds and orderly and organized library services. Apart from that, additional programs like group prayer activities, morning exercises, and Indonesian speeches exist.